Political Influence in a New Antidumping Regime: Evidence from Mexico - Joseph F. Francois; Gunnar Niels (Tinbergen Institute, 2004)
We examine the role of political factors in Mexico's antidumping regime, considering both the characteristics of target countries subject to antidumping duties and industry-specific factors for sectors receiving protection. Our results are broadly consistent with the recent theoretical literature on endogenous protection, in terms of both the political costs and the political benefits of providing protection. They are also in line with the existing empirical literature on antidumping, which is focused primarily on the experience of the U.S. and the EU. Our results also suggest that WTO Membership of trading partners increases the political costs of supplying administered protection.
Keywords: F10; F13; 330; antidumping; political economy of trade policy; Mexico; endogenous import protection; endogenous tariffs; Antidumping; Importbeschränkung; Mexiko